Stimulasi perkembangan bahasa anak usia dini dengan riwayat stunting - Nurfia, Yulia Tutik (PSYCOMEDIA : Jurnal Psikologi, 2024)
This study aims to assess the impact of implementing language stimulation in early childhood with a history of stunting. This research focuses on early childhood suffering from stunting and wasting. This research uses qualitative methods with a case study research design. The results showed that vocabulary mastery is influenced by several factors including limited interaction and communication with the surrounding environment, lack of education and stimulus for children's vocabulary mastery. The results of this study also show that language stimulation in post-stunting children can help optimize children's brain function. Early childhood children who receive language stimulation tend to be more directed and experience improvements in recognizing new words and communication skills to become more confident in using words to express ideas and emotions.